2019
DOI: 10.1186/s12969-019-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

The time option of IVIG treatment is associated with therapeutic responsiveness and coronary artery abnormalities but not with clinical classification in the acute episode of Kawasaki disease

Abstract: Background In the last decade, incomplete Kawasaki disease (KD), intravenous immunoglobulin (IVIG) non-response and coronary artery abnormalities (CAA) have experienced the increasing trends in China. In addition, the enhancement of pediatricians’ awareness may also raise the diagnostic rate of incomplete KD and stimulate more aggressive initial therapy in the acute episode of KD. Given this background, we hypothesize that the time option of IVIG treatment should be in parallel with peak time of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Children with KD often show elevated WBC, PLT, accelerated ESR, elevated CRP level, abnormal liver function, and abnormal urine test. [ 1 , 18 ] Although they cannot be used as diagnostic indicators alone, their changes are helpful for the early diagnosis of IKD. The results of this study showed that the laboratory indexes of KD children, such as CRP, WBC, ESR, ALB, HCT, PLT, ALT, AST, NT-proBNP, Hb, NEUT, had some changed when compared with the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Children with KD often show elevated WBC, PLT, accelerated ESR, elevated CRP level, abnormal liver function, and abnormal urine test. [ 1 , 18 ] Although they cannot be used as diagnostic indicators alone, their changes are helpful for the early diagnosis of IKD. The results of this study showed that the laboratory indexes of KD children, such as CRP, WBC, ESR, ALB, HCT, PLT, ALT, AST, NT-proBNP, Hb, NEUT, had some changed when compared with the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the timing of IVIG treatment influenced the reactivity to treatment regardless of the severity of KD. Besides, It was reported that in patients with KD, inflammatory mediators, including plasma white blood cell count, absolute neutrophil count, and CRP peak within 5–10 days of KD onset, thus, the inappropriate timing of IVIG treatment may lead to an increased incidence of IVIG unresponsiveness ( 47 ). However, owing to the potential confounders between groups, subsequent studies are still needed to focus on controlling for differences in patients' baseline characteristics in order to obtain reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…We treated our patient with a second dose of IVIG along with steroids (2 mg/kg) with a full clinical response. Recent studies have also found that the incidence of coronary artery lesions (CAL) varies significantly depending on the timing of IVIG treatment, suggesting that early use of IVIG is an effective method to inhibit systemic inflammation and prevent CAL [ 18 ].…”
Section: Discussionmentioning
confidence: 99%